Relationships between energy cost, swimmming velocity and speed fluctuation in competitive swimming strokes - Barbosa, T. M.; Lima, F.; Portela, A.; Novais, D.; Machado, L.; Colaco, P.; Goncalves, R. F.; Keskinen, K. L.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the study was to analyse relationships between total energy expenditure (Etot), energy cost (EC), intracycle Variation of the horizontal velocity of displacement of centre of mass (dv) and mean swimming velocity (v). 17 Portuguese elite swimmers (4 at Freestyle, 5 at Backstroke, 4 at Breaststroke and 4 at Butterfly) were submitted to an incremental set of nx200-m swims. Bioenergetical and biomechanical parameters presented significant interrelationships. For pooled data, the relationship between Eto, and v was r=0.59 (p<0.01), between EC and dv was r=0.38 (p<0.01) and the polynomial relationship, between dv and v was r=0.17 (p=0.28). Individual evaluation and identification of biomechanical critical points may help the swimmers to become more efficient at a certain swimming velocity.